Investigating Public Awareness and Attitudes towards People with Bipolar Disorder in Punjab, Pakistan: A Cross-Sectional Study: Investigating Public Awareness and Attitudes with Bipolar Disorder - Hussain, Muzamal; Ullah, Obaid; Kanwal, Nazia; Mohsin, Hareem; Hanif, Nimra; Zakir, Sadia; Manzoor, Maleeha; Zahid, Laiba (Pakistan Journal of Health Sciences, 2023)
Bipolar Disorder (BP) is a psychiatric disorder that causes severe mood swings. As the leading cause of cognitive impairment, it affects many people worldwide. This study examines public awareness and attitudes towards bipolar disorder BP in Punjab, Pakistan, highlighting a literature gap. Non-professional community views and stigmatization of BP are examined in the specified region of Pakistan. Objective: To understand risk aspects to create a supportive environment for BP patients and informing future awareness and education efforts. Methods: This study used a validated questionnaire that included sociodemographic factors such as age, gender, degree of education, and employment status. The questionnaire was based on general, medical, and social categories. Responses for all sections were either "Agree," "Disagree," or "Do not know." These answers were assessed using computing language 1 = Agree, 0 = Disagree, and 2 = Do not Know. Python was used for data analysis in this study. Results: The study found that despite some awareness, there were significant misconceptions and negative attitudes toward those living with the disorder. Overall, the study states a low level of awareness regarding bipolar disorder among the surveyed population, with only around 48% having high awareness and positive attitudes toward bipolar disorder sufferers. Conclusions: Current research findings significantly affect Pakistan’s mental health policy and education. Improving public understanding and reducing stigma surrounding mental health issues is crucial for ensuring that those with bipolar disorder and other mental health conditions can access the care and support they need.